Pelatihan Abon Kates (Bontes) sebagai Daya Tarik Wisata kuliner di Padukuhan Klepu Lor Sendang Mulyo Minggir Sleman Yogyakarta - Lutfi Hendriyati; Heni Widyaningsih; Hery Krestanto; Annisa Grace; Ihsan Budi Santoso (Sekolah Tinggi Pariwisata AMPTA Yogyakarta, 2023)
The purpose of this community service is to increase public knowledge about kates processing by making shredded and increasing knowledge about the packaging of shredded papaya products so that they can be sold as souvenirs and as a culinary tourist attraction from the Klepu Lor village. This training is intended for women who are members of the Klepu Lor Padukuhan UKM who are located at Klepu Lor Padukuhan, Sendangmulyo, Minggir, Sleman. The method used in the training for making shredded kates (Bontes) uses the Lecture and Hands-on Practice method. The outputs of this community service activity are (1) Increasing knowledge that papaya fruit can be used to be processed into food; (2) Increasing the creativity and product innovation of Klepu Lor Padukuhan UMKM by processing papaya fruit into shredded kates; (3) Increase knowledge and skills in processing papaya which can be used as a source of family income. The positive impact of this community service on shredded kates processing is that housewives who are members of the Padukuhan Klepu Lor MSME group have the knowledge and insight to utilize their yards by planting papayas (Kates).